Development of Predictive Equations for Nocturnal Hypertension and Nondipping Systolic Blood Pressure. Issue 2 (21st January 2020) - Jaeger, Byron C.; Booth, John N.; Butler, Mark; Edwards, Lloyd J.; Lewis, Cora E.; Lloyd‐Jones, Donald M.; Sakhuja, Swati; Schwartz, Joseph E.; Shikany, James M.; Shimbo, Daichi; Yano, Yuichiro; Muntner, Paul
Abstract : Background: Nocturnal hypertension, defined by a mean asleep systolic blood pressure (SBP)/diastolic blood pressure (BP) ≥120/70 mm Hg, and nondipping SBP, defined by an awake‐to‐asleep decline in SBP <10%, are each associated with increased risk for cardiovascular disease. Methods and Results: We developed predictive equations to identify adults with a high probability of having nocturnal hypertension or nondipping SBP using data from the CARDIA (Coronary Artery Risk Development in Young Adults) study (n=787), JHS (Jackson Heart Study) (n=1063), IDH (Improving the Detection of Hypertension) study (n=395), and MHT (Masked Hypertension) study (n=772) who underwent 24‐hour ambulatory BP monitoring. Participants were randomized to derivation (n=2511) or validation (n=506) data sets. The prevalence rates of nocturnal hypertension and nondipping SBP were 39.7% and 44.9% in the derivation data set, respectively, and 36.6% and 44.5% in the validation data set, respectively. The predictive equation for nocturnal hypertension included age, race/ethnicity, smoking status, neck circumference, height, high‐density lipoprotein cholesterol, albumin/creatinine ratio, and clinic SBP and diastolic BP. The predictive equation for nondipping SBP included age, sex, race/ethnicity, waist circumference, height, alcohol use, high‐density lipoprotein cholesterol, and albumin/creatinine ratio. Concordance statistics (95% CI) for nocturnal hypertension and nondipping SBP predictive equations in the validation data set were 0.84 (0.80–0.87) and 0.73 (0.69–0.78), respectively. Compared with reference models including antihypertensive medication use and clinic SBP and diastolic BP as predictors, the continuous net reclassification improvement (95% CI) values for the nocturnal hypertension and nondipping SBP predictive equations were 0.52 (0.35–0.69) and 0.51 (0.34–0.69), respectively. Conclusions: These predictive equations can direct ambulatory BP monitoring toward adults with high probability of having nocturnal hypertension and nondipping SBP.